Specification for thermal spray feedstock--wire and rods (American Welding Society, 2012)
This specification prescribes requirements for the classification of thermal spray feedstock based on the as manufactured chemical composition. Thermal Spray Feedstock includes solid and composite wires and ceramic rods for thermal spraying. Requirements for standard sizes, marking, manufacturing, and packaging are included.
"An American national standard."
"Supersedes AWS C2.25/C2.25M:2002."
"Approved by American National Standards Institute September 5, 2012."
Keywords: Electric welding -- Specifications.; Metal spraying -- Specifications.; Wire bonding (Electronic packaging) -- Specifications.; elektronické knihy; electronic books